ALK rearrangement in lung adenocarcinoma with concurrent cervix and breast metastases: A case report. Issue 11 (24th August 2018) - Chuang, Xin; Chen, Ying; Yu, Ping; Qiu, Xueshan; Wang, Jian; Qu, Xiujuan; Teng, Yuee; Liu, Yunpeng; Jin, Bo
Abstract : Distant metastases of pulmonary adenocarcinoma are regularly observed in the bones, brain, adrenal gland, and liver, but rarely in the breast or cervix. In this report, we describe a novel case of concurrent cervix and breast metastases from lung adenocarcinoma, with ALK rearrangements that were strongly consistent between the primary and metastatic cancers. A 44‐year‐old Chinese woman with a chief complaint of abdominal discomfort was referred to our hospital. Based on diagnostic imaging, pathology, immunohistochemistry, and next‐generation sequencing, the patient was diagnosed with lung adenocarcinoma with breast and cervical metastases, and ALK rearrangements were found in all three lesions. The patient was prescribed crizotinib as first‐line treatment, which showed a steady reduction of the lung lesion. To our knowledge, this is the first report of concurrent breast and cervical metastases from lung adenocarcinoma. We conclude that physicians should consider that metastases may invade the breast and cervix uteri when making a diagnosis.